2007
DOI: 10.1017/s0007114507685195
|View full text |Cite
|
Sign up to set email alerts
|

Personalised nutrition: status and perspectives

Abstract: Personalised, genotype-based nutrition is a concept that links genotyping with specific nutritional advice in order to improve the prevention of nutrition-associated, chronic diseases. This review describes the current scientific basis of the concept and discusses its problems. There is convincing evidence that variant genes may indeed determine the biological response to nutrients. The effects of single-gene variants on risk or risk factor levels of a complex disease are, however, usually small and sometimes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 37 publications
0
67
0
1
Order By: Relevance
“…In recent years, there is increasing public interest in genetic testing in the health field, in a study investigating attitudes to genetic testing among 2000 individuals, 81 % of respondents believed that knowing their genetic risk could lead to better control of their lives (108) . A number of studies have reported that individuals identified as having a higher disease risk through genetic testing may be more motivated to change dietary habits (109)(110)(111) . Nevertheless a number of concerns towards genetic testing have been reported including cost, privacy, misuse of genetic information and fear that results could influence insurance companies and job opportunities (107,108,110,112) .…”
Section: Mechanism Of Mthfr C677t Polymorphism Riboflavin and Blood mentioning
confidence: 99%
“…In recent years, there is increasing public interest in genetic testing in the health field, in a study investigating attitudes to genetic testing among 2000 individuals, 81 % of respondents believed that knowing their genetic risk could lead to better control of their lives (108) . A number of studies have reported that individuals identified as having a higher disease risk through genetic testing may be more motivated to change dietary habits (109)(110)(111) . Nevertheless a number of concerns towards genetic testing have been reported including cost, privacy, misuse of genetic information and fear that results could influence insurance companies and job opportunities (107,108,110,112) .…”
Section: Mechanism Of Mthfr C677t Polymorphism Riboflavin and Blood mentioning
confidence: 99%
“…Robust and validated data are difficult to obtain, because of the limited availability of biomarkers of health as well as the high cost of human nutrigenomics intervention studies (20) . However, companies argue there are significant benefits of genotype-based personalised nutrition.…”
Section: Development Of Diet and Lifestyle Assessment Testsmentioning
confidence: 99%
“…These challenges will include feeding the growing and ageing world population, better and sustainable use of natural resources as well as improving our ability to exploit foods' potential to prevent diseases and maintain health promote wellness. In this respect, personalized or tailored nutrition seem highly promising and challenging strategies (Joost et al, 2007;Qi, 2014;Zeevi et al, 2015). Such endeavors will require bridging manufacturing capabilities and product engineering to meet the specific needs of the consumer.…”
Section: Rationale and Approach For Extending Ivd Modelsmentioning
confidence: 99%